Definite total radical resection in treatment of patients, suffering low-differentiated cancer of the bladder - P. G. Yakovlev (Клінічна хірургія)
Objective. To determine the operative volume of surgical treatment in total radical resection of the bladder in autonomous regime and to estimate the survival indices in patients with low-differentiated cancer of the bladder depending on time of conduction of radical total resection of the bladder.